Complete Life Cycle of Trypanosoma thomasbancrofti, an Avian Trypanosome Transmitted by Culicine Mosquitoes - Fialová, Magdaléna; Santolíková, Anežka; Brotánková, Anna; Brzoňová, Jana; Svobodová, Milena (Microorganisms, 2021)
Avian trypanosomes are cosmopolitan and common protozoan parasites of birds; nevertheless, knowledge of their life cycles and vectors remains incomplete. Mosquitoes have been confirmed as vectors of Trypanosoma culicavium and suggested as vectors of T. thomasbancrofti; however, transmission has been experimentally confirmed only for the former species. This study aims to confirm the experimental transmission of T. thomasbancrofti to birds and its localization in vectors. Culex pipiens were fed on blood using four strains of T. thomasbancrofti, isolated from vectors and avian hosts; all strains established infections, and three of them were able to develop high infection rates in mosquitoes. The infection rate of the culicine isolates was 5-28% for CUL15 and 48-81% for CUL98, 67-92% for isolate OF19 from hippoboscid fly, while the avian isolate PAS343 ranged between 48% and 92%, and heavy infections were detected in 90% of positive females. Contrary to T. culicavium, trypanosomes were localized in the hindgut, where they formed rosettes with the occurrence of free epimastigotes in the hindgut and midgut during late infections. Parasites occurred in urine droplets produced during mosquito prediuresis. Transmission to birds was achieved by the ingestion of mosquito guts containing trypanosomes and via the conjunctiva. Bird infection was proven by blood cultivation and xenodiagnosis; mature infections were present in the dissected guts of 24-26% of mosquitoes fed on infected birds. The prevalence of T. thomasbancrofti in vectors in nature and in avian populations is discussed in this paper. This study confirms the vectorial capacity of culicine mosquitoes for T. thomasbancrofti, a trypanosome related to T. avium, and suggests that prediuresis might be an effective mode of trypanosome transmission.
Keywords: prediuresis; life cycle; Trypanosoma thomasbancrofti; avian parasite; transmission; Culex; mosquito